The Effectiveness of the FX Market Interventions of the Bundesbank During the Louvre Period: An Options-Based Analysis - Christian Pierdzioch (Kiel Institute of World Economics (IfW), 2000)
The effectiveness of the foreign exchange market interventions conducted by the Deutsche Bundesbank during the Louvre period to alter either the level or the volatility of the /DM spot rate is examined. Volatility quotes implicit in foreign currency options are employed to recover the impact of interventions on the variability of exchange rates. A contingent claims valuation framework allowing to highlight the implications of infrequent interventions for the valuation of options on foreign currency is constructed. The impact of interventions on FX option premia in a regime characterized by infrequent interventions and implicit intervention thresholds and in a pure managed float system is analyzed. A multifactor success criterion is developed to assess the effectiveness of the forex interventions of the Bundesbank empirically within the context of a qualitative dependent variable model.
Keywords: G13; F31; 330; Central Bank Interventions; Foreign Currency Options; Implied Volatility; Ordered Probit Model; Wechselkurspolitik; Wirtschaftspolitische Wirkungsanalyse; Wechselkurs; Volatilität; Devisenoptionsgeschäft; Optionspreistheorie; Probit-Modell; Schätzung; Theorie; Deutschland; Vereinigte Staaten